THE ROLE OF PROFESSORS AND TEACHERS IN MEDICAL TECHNICAL SCHOOLS - Boboyeva, Nigora Sodikovna (Educational Research in Universal Sciences, 2024)
In this article, the role of professors and teachers in medical technical schools is important in preparing future healthcare professionals with the necessary knowledge, skills and qualifications to achieve high results in their fields. characteristics are revealed. In this process, it was emphasized that teachers play an important role in providing comprehensive and modern education, mentoring students, conducting scientific research and improving educational culture.